STRATEGI KEPALA MADRASAH DALAM MENINGKATKAN CITRA POSITIF DAN PRESTASI MELALUI KELAS UNGGULAN DI MA AL- AMIRIYYAH BLOKAGUNG BANYUWANGI - Moh Harun Al Rosid; Latifatul Fauziyah (Institut Agama Islam Darussalam Blokagung, 2022)
The research focus in this paper is: (1) what is the principal's strategy in improving a positive image through superior classes at MA al-Amiriyyah Blokagung Banyuwangi? (2) what is the madrasa principal's strategy for improving achievement through a superior class at MA al-Amiriyyah Blokagung Banyuwangi? (3) what are the supporting and inhibiting factors for the madrasa principal's strategy in improving a positive image and achievement through a superior class at MA al-Amiriyyah Blokagung Banyuwangi? The purpose of this research is to determine the achievement through superior class and to find out the supporting and inhibiting factors of the madrasa principal's strategy in increasing the positive image and achievement through the superior class. The method used by the researcher here is a qualitative approach with a qualitative descriptive type of research. The location of this research is MA al-Amiriyyah Blokagung, Tegalsari sub-district, Banyuwangi district, East Java, from 1 to 14 March. The research subjects were the head of the madrasa as the leader who managed everything in the madrasa and MA al-Amiriyyah students and the community or parents of MA al-Amiriyyah students. Data collection techniques are observation, interviews, and documentation. While the data analysis is an interaction analysis of 3 models of Milles and Huberman, namely data reduction, data presentation, drawing conclusions, and also SWOT analysis is used to determine the supporting and inhibiting factors.